A preparation method of a heterogeneous structure material and its application in lithium battery negative electrode
By designing heterostructures in the negative electrode material of lithium-ion battery and coupling inorganic materials with different band gaps, the volume expansion problem caused by metal agglomeration during the circulation process is solved, and the circulation stability and rate performance of the material are significantly improved.
Patent Information
- Application Number
- CN202110939968.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-16
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2041-08-16
AI Technical Summary
The existing lithium-ion battery anode material expands volume during the circulation process due to metal agglomeration, which in turn damages the solid electrolyte interface and reduces the specific capacity and cycle stability of the material.
Using heterostructure design, the heterostructure of MOx/MSx is formed by coupling inorganic materials with different band gaps, thereby improving the surface reaction kinetics and charge transfer, and solving the volume expansion problem.
It significantly improves the cycle stability and rate performance of the negative electrode material of lithium-ion battery, enhances the specific capacity, and extends the cycle life of the battery.
Smart Images

Figure CN115706214B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion batteries, and specifically to a heterostructured negative electrode material with high specific capacity, high rate performance, and excellent cycle stability, as well as a preparation method and application thereof. Technical Background
[0002] In order to build high energy density and high power density lithium-ion batteries, it is of great significance to develop high capacity and high rate performance lithium battery negative electrode materials. Among several types of lithium battery negative electrodes, traditional conversion-alloying negative electrodes (oxides or sulfides of Zn, Cd, Ga, In, Ge, Sn, etc.) have attracted much attention from researchers due to their high theoretical specific capacity and moderate charging median voltage. The chemical reaction of the conversion-alloying negative electrode usually follows the following two reaction steps (taking metal oxides as an example): MQ x +2xLi + +2xe - →M+xLi2Q(Q=O,S,Se), conversion reaction; Alloying-dealloying reaction. However, the first step of the conversion reaction is usually irreversible, mainly because the conductivity of this type of material is poor, which prevents it from reacting isotropically. In the second step of the reversible alloying-dealloying process, the metal M agglomerates to form a larger metal domain, resulting in volume expansion, which in turn leads to the destruction of the solid electrolyte interface (SEI) and the gradual inactivation of the electrode material.
[0003] Usually, the deactivation of the conversion reaction will cause the specific capacity of the electrode material to be greatly discounted, at least to less than 50% of the theoretical value. In order to solve the problem of metal agglomeration during the electrode cycle, many strategies have been developed. The introduction of transition metals (Fe, Co, Ni or Mn) into this type of negative electrode material can greatly improve the electronic conductivity of the material, thereby alleviating metal agglomeration; however, the introduction of transition metals also increases the charging median voltage of the material, reducing its energy density and power density. Another common strategy is to introduce carbon materials (graphene, graphene oxide, carbon nanotubes, etc.) into the electrode. Carbon materials can effectively disperse active electrode materials and act as a conductive framework to effectively avoid metal agglomeration; however, the introduction of carbon materials will inevitably reduce the compaction density of the material, resulting in a lower volume energy density of the electrode.
[0004] In summary, the field urgently needs to develop a conversion-alloying type negative electrode material with high specific capacity and high cycle stability that can overcome the above-mentioned defects. Based on the latest research progress in the field of materials science, the present invention combines the design concept of inorganic heterostructures in the optoelectronic field, couples inorganic materials with different band gaps, and proposes a design concept of energy storage type inorganic heterostructures. While promoting interfacial charge transfer, it improves the surface reaction kinetics and successfully constructs a series of high-performance conversion-alloying materials. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a heterostructure and its application as a negative electrode for lithium-ion batteries. The construction of the heterostructure can effectively improve the surface reaction kinetics and promote charge transfer; the various surface Li-containing matrices formed can effectively solve the volume expansion problem of conversion-alloying type materials during the cycle, thereby improving the cycle stability and rate performance of lithium batteries.
[0006] In the first aspect, the present invention provides a heterostructure material for lithium-ion battery negative electrode material, the chemical composition of which is MO x / MS x , wherein M is selected from one or a combination of Zn, Cd, Ga, In, Ge, Sn, and x is the number of O or S anions contained, and the value is equal to half of the valence state corresponding to the metal M. The heterostructure has a rod-like, sheet-like, spherical, and other morphologies.
[0007] In a second aspect, the present invention provides a method for preparing any of the above-mentioned synthetic oxysulfide precursors, comprising: preparing a metal oxysulfide by mixing a metal salt and sulfur powder: ultrasonically dispersing the metal salt and sulfur powder in an alcohol solvent at a molar ratio of 1:1 to 1:3, stirring and ultrasonically dispersing, and reacting at 150 to 200°C for 10 to 120 minutes; standing, washing with water and ethanol twice respectively, and drying in an oven to obtain a metal oxysulfide precursor.
[0008] The metal salt is at least one of nitrate, chloride, sulfate, acetate and acetylacetonate of Zn, Cd, Ga, In, Ge and Sn.
[0009] The alcohol solvent is at least one of ethylene glycol, diethylene glycol, polyethylene glycol 200-1000, glycerol, isopropanol, n-butanol and n-hexanol.
[0010] In a third aspect, the present invention provides a method for preparing a heterostructure material for a negative electrode of a lithium-ion battery, wherein the metal oxysulfide precursor obtained above is placed in an inert atmosphere and subjected to heat treatment to obtain a heterostructure negative electrode material.
[0011] In the heterostructure lithium battery negative electrode material, MS x with MO x The molar ratio of is 10:1 to 1:5, and there is a rich heterogeneous interface between the two.
[0012] In the method for preparing the heterogeneous structure material, the inert atmosphere includes one of helium, argon, and nitrogen, or a mixture of the above gases.
[0013] In the preparation method of the heterogeneous structure material, the heat treatment temperature is 400-1000° C., the treatment time is 0.5-12 hours, and the heating rate is 1-30° C. / min.
[0014] In a fourth aspect, the present invention provides a method for preparing a heterostructure and its application in a lithium battery negative electrode, and its application is not limited to lithium-ion batteries, but can also be applied to sodium-ion batteries, potassium-ion batteries, zinc-ion batteries, supercapacitors, lithium-sulfur batteries and sodium-sulfur batteries.
[0015] Therefore, the present invention provides a heterostructure material for lithium-ion battery negative electrode material, the chemical composition is, wherein MO x / MS x , where M is selected from one or a combination of Zn, Cd, Ga, In, Ge, Sn, and x is the number of O or S anions contained, which is equal to half of the valence state of metal M. It is used as negative electrode material for lithium batteries, has high capacity and high rate stability, and has broad application prospects in power batteries and other fields. In this type of heterostructure, MS x with MO x The molar ratio of ZnO / ZnS is 10:1 to 1:5, and the shapes are rod-shaped, flake-shaped, spherical, etc. Tests show that ZnO / ZnS, as an example, has better capacity and cycle stability as anode materials for lithium batteries; at 0.1A g -1 At the current density, after 100 cycles, it has 1213mA hg -1 The specific capacity at 2A g -1 At the current density, it still has 920mA hg after 1300 cycles. -1 The specific capacity of the lithium ion battery is much higher than the theoretical specific capacity. The present invention provides a heterostructure material for the negative electrode of a lithium ion battery, which has the characteristics of high specific capacity and high rate stability and is suitable for large-scale commercial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is a powder X-ray diffraction pattern of the ZnO / ZnS heterostructure in Example 1 of the present invention;
[0017] Figure 2 The transmission electron microscope-element spectrum diagram of the ZnO / ZnS heterostructure in Example 1 of the present invention;
[0018] Figure 3 This is a transmission electron microscope image of the ZnO / ZnS heterostructure in Example 1 of the present invention;
[0019] Figure 4 The selected fast Fourier transform image analysis and element distribution diagram corresponding to the transmission electron microscope image of the ZnO / ZnS heterostructure in Example 1 of the present invention;
[0020] Figure 5 The ZnO / ZnS heterostructure in Example 1 of the present invention is 0.1Ag -1 Cyclic stability under
[0021] Figure 6 The ZnO / ZnS heterostructure in Example 1 of the present invention at 2A g -1 High rate stability under high magnification;
[0022] Figure 7 The ZnO in Example 2 of the present invention is 0.1A g -1 High rate stability under high magnification;
[0023] Figure 8 The ZnS in Example 3 of the present invention is 0.1A g -1 High rate stability under high magnification;
[0024] Fig. 9 The SnO2 / SnS2 heterostructure in Example 4 of the present invention is 0.1A g -1 Cyclic stability under
[0025] Fig.10 The SnO2 / SnS2 heterostructure in Example 4 of the present invention is 1A g -1 High rate stability under high magnification;
[0026] Fig.11 The In2O3 / In2S3 heterostructure in Example 5 of the present invention is 0.1A g -1 Cyclic stability under
[0027] Fig.12 The In2O3 / In2S3 heterostructure in Example 5 of the present invention at 1A g -1 High rate stability under high magnification. DETAILED DESCRIPTION
[0028] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention. In the following examples, the reagents, materials and instruments used are conventional reagents, conventional materials and conventional instruments unless otherwise specified, and can be obtained commercially.
[0029] The preparation and performance of the heterostructure negative electrode material of the present invention are further described below through specific examples. It should be understood that the specific parameters and the like in the following examples are only reasonable examples and are not limited to the specific values in the following examples.
[0030] Example 1
[0031] Preparation and properties of ZnO / ZnS heterostructure. (1) Synthesis of zinc oxysulfide precursor: Weigh 2mmol zinc acetate and 2mmol sulfur powder in 40mL PEG-200, stir and ultrasonically disperse, and react at 180℃ for 40min; let stand, wash in the order of ethanol-water-water-ethanol, wash 4 times in total, and dry in an oven to obtain a metal oxysulfide precursor. (2) Synthesis of ZnO / ZnS heterostructure: Place the zinc oxysulfide precursor obtained above in an argon atmosphere, heat to 700℃ at a rate of 13° / min, and heat treat for 2h to obtain a ZnO / ZnS heterostructure negative electrode material.
[0032] Through the powder X-ray diffraction test of ZnO / ZnS, it is proved that the heterostructure has cubic ZnS (c-ZnS), hexagonal ZnS (h-ZnS) and hexagonal ZnS (h-ZnO), such as Figure 1 shown.
[0033] The chemical composition of ZnO / ZnS was determined by transmission electron microscopy-element distribution mapping, and the molar ratio of ZnS to ZnO in the heterostructure was 4:1, as shown in Figure 2 shown.
[0034] ZnO / ZnS heterostructures present a nanosheet structure, such as Figure 3 In addition, by performing fast Fourier transform on ZnO / ZnS, the coexistence of cubic ZnS (c-ZnS), hexagonal ZnS (h-ZnS) and hexagonal ZnS (h-ZnO) was confirmed, and the phase interface in the heterostructure was confirmed, as shown in Figure 4 shown.
[0035] ZnO / ZnS heterostructure at 0.1A g -1 At the current density, after 100 cycles, it has 1199.2mA hg -1 The specific capacity, such as Figure 5 As shown; at 2A g -1 At the current density, it still has 920.0mA hg after 1300 cycles. -1 The specific capacity is much higher than its theoretical specific capacity (ZnO: 988mA hg -1 , ZnS:825mA hg -1 ),like Figure 6 shown.
[0036] Example 2
[0037] ZnO / ZnS heterostructure comparison sample - synthesis and performance of ZnO. 40 mg of the ZnO / ZnS heterostructure material obtained in Example 1 was placed in 80 mL of 2M KOH solution for reaction for 1 hour. The obtained product was centrifuged and washed with deionized water 3 times to obtain a pure ZnO phase sample. Its performance is as follows Figure 7 As shown, at 0.1Ag -1 At the current density, after 100 cycles, it has 99.1mA hg -1 Specific capacity.
[0038] Example 3
[0039] ZnO / ZnS heterostructure comparison sample - synthesis and performance of ZnS. The ZnO / ZnS heterostructure material obtained in Example 1 was placed in a porcelain boat and calcined at 440°C for 12 hours in an air atmosphere to obtain a ZnS pure phase sample. Its performance is as follows Figure 8 As shown, at 0.1A g -1 At the current density of 50.0 mAh g -1 Specific capacity.
[0040] Example 4
[0041] Preparation and properties of SnO2 / SnS2 heterostructure. (1) Synthesis of tin oxysulfide precursor: Weigh 2mmol of stannous acetate and 4mmol of sulfur powder in 40mL of PEG-200, stir and ultrasonically disperse, and react at 180℃ for 40min; let stand, wash in the order of ethanol-water-water-ethanol, wash 4 times in total, and dry in an oven to obtain a metal oxysulfide precursor. (2) Synthesis of SnO2 / SnS2 heterostructure: Place the zinc oxysulfide precursor obtained above in an argon atmosphere, heat to 500℃ at a rate of 9° / min, and heat treat for 2h to obtain a SnO2 / SnS2 heterostructure negative electrode material.
[0042] SnO2 / SnS2 heterostructure at 0.1A g -1 At the current density, after 50 cycles, it has 1186.7mA hg -1 The specific capacity, such as Fig. 9 As shown; at 1A g -1 At the current density, it still has 1084.7mA hg after 700 cycles. -1 The specific capacity, such as Fig.10 shown.
[0043] Example 5
[0044] Preparation and properties of In2O3 / In2S3 heterostructure. (1) Synthesis of indium oxysulfide precursor: Weigh 2mmol indium acetate and 3mmol sulfur powder in 40mL PEG-200, stir and ultrasonically disperse, and react at 180℃ for 40min; let stand, wash in the order of ethanol-water-water-ethanol, wash 4 times in total, and dry in an oven to obtain a metal oxysulfide precursor. (2) Synthesis of In2O3 / In2S3 heterostructure: Place the zinc oxysulfide precursor obtained above in an argon atmosphere, heat to 600℃ at a rate of 11° / min, and heat treat for 2h to obtain an In2O3 / In2S3 heterostructure negative electrode material.
[0045] In2O3 / In2S3 heterostructure at 0.1A g -1 At the current density of 858.6 mAh g after 90 cycles -1 The specific capacity, such as Fig.11 As shown; at 1A g -1 At the current density, it still has 920.4mA hg after 1500 cycles. -1 The specific capacity is much higher than its theoretical specific capacity (In2O3: 965mA hg -1 ,In2S3:822mA hg -1 ),like Fig.12 shown.
[0046] Example 6
[0047] Preparation and properties of CdO / CdS heterostructure. (1) Synthesis of cadmium oxysulfide precursor: Weigh 2mmol cadmium acetate and 2mmol sulfur powder in 40mL PEG-200, stir and ultrasonically disperse, and react at 180℃ for 40min; let stand, wash in the order of ethanol-water-water-ethanol, wash 4 times in total, and dry in an oven to obtain a metal oxysulfide precursor. (2) Synthesis of CdO / CdS heterostructure: Place the cadmium oxysulfide precursor obtained above in an argon atmosphere, heat to 500℃ at a rate of 9° / min, and heat treat for 2h to obtain a CdO / CdS heterostructure negative electrode material.
[0048] Example 7
[0049] Preparation and properties of GeO2 / GeS2 heterostructure. (1) Synthesis of cadmium oxysulfide precursor: Weigh 2mmol germanium acetate and 4mmol sulfur powder in 40mL PEG-200, stir and ultrasonically disperse, and react at 180℃ for 60min; let stand, wash in the order of ethanol-water-water-ethanol, wash 4 times in total, and dry in an oven to obtain a metal oxysulfide precursor. (2) Synthesis of GeO2 / GeS2 heterostructure: Place the above-obtained germanium oxysulfide precursor in an argon atmosphere, heat to 700℃ at a rate of 13° / min, and heat treat for 4h to obtain a GeO2 / GeS2 heterostructure negative electrode material.
[0050] The method for preparing the negative electrode material of lithium battery in Examples 1-5 is as follows: the above-mentioned example materials are uniformly mixed with acetylene black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 8:1:1, and NMP (N-methylpyrrolidone) is added to form a slurry. Stir overnight, apply a 100μm scraper on a 9μm Cu foil, and vacuum dry the electrode sheet at 80°C for 12 hours. The battery is encapsulated in an argon circulating glove box, the negative electrode is a Li sheet, and the diaphragm uses a Whatman glass fiber membrane. The electrolyte used is 1MLiPF6 dissolved in ethyl carbonate (EC) and diethyl carbonate (DEC), containing 10% fluoroethylene carbonate (FEC) and 1.0% vinyl carbonate (VC). The electrochemical performance test was carried out on a LAND battery tester, with a charge and discharge voltage range of 0.01-3.0V and a current density of 0.1A g -1 , 1A g -1 or 2A g -1 .
[0051] The lithium battery negative electrode performance of the heterogeneous structure materials of Examples 1, 4, and 5 is summarized in Table 1-2, indicating that the synthesis process of the present invention has a universal method. At the same time, compared with Examples 2 and 3, the heterogeneous structure negative electrode material exhibits excellent electrochemical performance, further proving the importance of heterogeneous structure negative electrode material design.
[0052] Table 1 Comparison of negative electrode cycling performance of heterogeneous lithium batteries (voltage window 0.01-3V, current density 0.1A g -1 )
[0053]
[0054]
[0055] Table 2 Comparison of high rate stability of negative electrodes of heterogeneous lithium batteries (voltage window 0.01-3V)
[0056]
[0057] The above embodiments are limited to further illustrating the present invention and are illustrative rather than restrictive. Under the inspiration of the present invention, those skilled in the art may make many substitutions or modifications without departing from the scope of the present invention and the scope of protection of the claims, and any non-essential improvements and adjustments made belong to the protection scope of the present invention.
Claims
1. A heterostructure material for a negative electrode of a lithium-ion battery, characterized in that: (1) The chemical composition of the heterostructure material is MO x / MS x , wherein M is selected from one or a combination of Zn, Cd, Ga, In, Ge, Sn, and x is the number of O or S anions contained, and the value is equal to half of the valence state corresponding to the metal M; (2) The heterostructure material has a rod-like, sheet-like, or spherical morphology; The method for preparing the heterogeneous structure material comprises the following two steps: (1) Preparation of metal oxysulfide: ultrasonically disperse metal salt and sulfur powder in a certain ratio in polyethylene glycol 200-1000, stir and ultrasonically disperse, react at 150-200° C. for 10-120 min; let stand, wash with water and ethanol twice respectively, and dry in an oven to obtain a metal oxysulfide precursor; (2) Preparation of heterostructure material: placing the metal oxysulfide precursor in an inert atmosphere and performing heat treatment to obtain the heterostructure material.
2. The heterostructure material according to claim 1, characterized in that: The metal salt is at least one of nitrate, chloride, sulfate, acetate and acetylacetonate of Zn, Cd, Ga, In, Ge and Sn.
3. The heterostructure material according to claim 1, characterized in that: The molar ratio of the metal salt to the sulfur powder is 1:1 to 1:
3.
4. The heterostructure material according to claim 1, characterized in that: The temperature of the heat treatment is 400-1000° C., and the time of the heat treatment is 0.5-12 hours.
5. The heterostructure material according to claim 1, characterized in that: During the heating process of the heat treatment, the heating rate is 1 to 30° C. / min.
6. The heterostructure material according to claim 1, characterized in that: The inert atmosphere includes one of helium, argon, nitrogen, or a mixture of the above gases.
7. The heterostructure material according to claim 1, characterized in that: MS x with MO x The molar ratio of is 10:1 to 1:5, and there is a rich heterogeneous interface between the two.
8. Use of the heterostructure material according to any one of claims 1 to 7 in a negative electrode of a battery, characterized in that: The batteries include lithium-ion batteries, sodium-ion batteries, potassium-ion batteries, zinc-ion batteries, lithium-sulfur batteries and sodium-sulfur batteries.
9. Use of the heterostructure material according to any one of claims 1 to 7 in a supercapacitor.
Citation Information
Patent Citations
Method for preparing C / ZnO / ZnS ternary nano composite by taking sodium lignin sulfonate as sulfur source
CN111330597A
ZnS@ZnO core-shell structure nanorod material, preparation method thereof and aqueous lithium ion battery
CN111403720A